Chapter Le reintegre o platee dei Sanseverino di Bisignano: diritti e prelievo signorile nella Calabria settentrionale (secolo XV - prima metà del XVI) - Riccardo Berardi (Reti Medievali E-Book, 2021)
The aim of this paper is to reassess the history of the Sanseverino family, princes of Bisignano in Calabria in the Late Middle Ages; by focusing on a specific and unpublished source: the so-called "reintegre or platee" as written in the first half of the 16th century. These are public sources mostly enlisting properties and benefits; they serve the purpose of re-possessing the privileges taken from the princes themselves over the previous century. The paper will therefore focus not only on the management and character of the seigneurial landholdings but also on the reconstruction of both the local networks of power exerted on the population and the local political system. It will shed new light on the still debated historiographical issue centered on the seigneurial authority in southern Italy by assessing its local rooting and pervasiveness since the 14th century.